Ketimpangan Pendapatan Penyebab Tidak Bahagia - Wahyudi, Heru; Tiara, Ages (Penerbit Goodwood, 2022)
Purpose: The purpose of this study was to examine the influence of economic and non-economic factors on the level of happiness of the population in the provinces of Java and Sumatra. Research methodology: The analytical method used in this study is the Panel Data Analysis method for 16 provinces in 2014 and 2017. Results: The results showed that there was a positive and significant relationship between income per capita and the average length of schooling on the level of happiness, while income inequality had a negative and significant effect on the level of happiness, and there was a positive and insignificant relationship between life expectancy and the Indonesian democracy index on the level of happiness of the population in the provinces of Java and Sumatra. Limitations: The limitation in this study is that only 2 years of observation are used for 10 provinces with panel data regression. Contribution: The results obtained from this study are expected to be one of the references in making policy directions based on the data presented to adjust the right policies, especially to increase the happiness of the population in Indonesia.